Monitoring soybean seed germination by calorimetry - Schabes, Fanny Isabel (2011)
A method to monitor seed germination that combines isothermal calorimetry and imbibition measurements is reported. Individual seeds of three cultivars of soybean seeds (A7636RG, Munasqa and DM5.8RR) and one of radish were used. Imbibition curves were performed on individual seeds in a germination chamber at 25 C. Calorimetric specific thermal power (p)–time (t) curves of germination were also obtained at 25 C for 10 or more individual seeds after 30 min of equilibration of the system. Calorimetric experiments of germination in 5 mM KCN were performed to estimate specific imbibitions enthalpies (Dih). The p–t curves could be extrapolated to t = 0 by relating the rate of water uptake as determined from imbibitions curves with p values. Then, p–t curves were integrated to determine the specific metabolic enthalpies Dh which in turn were related to the water content (WC) of seeds at the corresponding times. The method allows determination of specific enthalpy change due to germination, Dgh, which apparently is species related. Besides, the standard deviation (SD) of the Dgh value gives an indication of seed quality. On the other hand, the water content that seeds need to germinate and the moment at which seeds are fully imbibed can also be determined. This is very important when breeding new cultivars for water stress tolerance. The water content needed for each cultivar to germinate was 74, 57, 35 and 64% for soybean seeds cvs. A7636RG, Munasqa, DM5.8RR and radish, respectively.